Integral mission : a new paradigm for Latin American Pentecostals. - Alvarez, Miguel, 1956- (Regnum studies in mission., 2016)
This volume studies Pentecostalism in Latin America as a broad, diverse and multifaceted movement. It describes different features and colors that together shape its collective face. This is done from context to context, weaving various relationships with society and politics. Pentecostalism is situated as a collective actor embedded in a changing reality that blends various streams for theological reflection. The book explains how Pentecostals in Latin America connect to the topic of God's mission in the world today.